The regional growth and unemployment effects of Engineering & Technology and Economics education in Poland - Żyra, Joanna (Oddziaływanie edukacji technicznej i ekonomicznej na wzrost regionalny i bezrobocie w Polsce, 2022)
Using annual time series for the period 2000-2019, this article analyses educational effects of the Engineering & Technology and Economics fields of study for Poland. It was found that the long-term education effects (in levels) are in favour of the former, both in terms of regional output growth and reduction in the number of unemployed. The short-term effects (in the first indicated differences) on both regional growth and unemployment are negative, regardless of the field of study. As both fields of study have unfavourable growth effects in the first differences, it indicates insufficient quality of investments in the human capital.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 4, s. 186-198
Keywords: higher education; fields of study; regional growth; unemployment rate; Poland; edukacja wyższa; kierunki studiów; wzrost regionalny; stopa bezrobocia; Polska